Nuclear export of plant pararetrovirus mRNAs involves the TREX complex, two viral proteins and the highly structured 5′ leader region. Issue 15 (9th August 2021) - Kubina, Julie; Geldreich, Angèle; Gales, Jón Pol; Baumberger, Nicolas; Bouton, Clément; Ryabova, Lyubov A; Grasser, Klaus D; Keller, Mario; Dimitrova, Maria
Abstract: In eukaryotes, the major nuclear export pathway for mature mRNAs uses the dimeric receptor TAP/p15, which is recruited to mRNAs via the multisubunit TREX complex, comprising the THO core and different export adaptors. Viruses that replicate in the nucleus adopt different strategies to hijack cellular export factors and achieve cytoplasmic translation of their mRNAs. No export receptors are known in plants, but Arabidopsis TREX resembles the mammalian complex, with a conserved hexameric THO core associated with ALY and UIEF proteins, as well as UAP56 and MOS11. The latter protein is an orthologue of mammalian CIP29. The nuclear export mechanism for viral mRNAs has not been described in plants. To understand this process, we investigated the export of mRNAs of the pararetrovirus CaMV in Arabidopsis and demonstrated that it is inhibited in plants deficient in ALY, MOS11 and/or TEX1. Deficiency for these factors renders plants partially resistant to CaMV infection. Two CaMV proteins, the coat protein P4 and reverse transcriptase P5, are important for nuclear export. P4 and P5 interact and co-localise in the nucleus with the cellular export factor MOS11. The highly structured 5′ leader region of 35S RNAs was identified as an export enhancing element that interacts with ALY1, ALY3 and MOS11 in vitro . Graphical Abstract: